Unextended Complexes. (14th October 2016) - Pickup, Martin
Abstract : Extended simples are fruitfully discussed in metaphysics. They are entities which are located in a complex region of space but do not themselves have parts. In this paper, I will discuss unextended complexes: entities which are not located at a complex region of space but do themselves have parts. In particular, I focus on one type of unextended complex: pointy complexes (entities that have parts but are located at a single point of space). Four areas are indicated where pointy complexes might prove philosophically useful. Unextended complexes are therefore philosophically fruitful, in much the same way as extended simples.